The effectiveness of public health advertisements to promote health: a randomized-controlled trial on 794,000 participants - Yom-Tov, Elad; Shembekar, Jinia; Barclay, Sarah, Peter Muennig (NPJ Digital Medicine, 2018)
As public health advertisements move online, it becomes possible to run inexpensive randomized-controlled trials (RCTs) thereof. Here we report the results of an online RCT to improve food choices and integrate exercise into daily activities of internet users. People searching for pre-specified terms were randomized to receive one of several professionally developed campaign advertisements or the “status quo” (ads that would otherwise have been served). For 1-month pre-intervention and post-intervention, their searches for health-promoting goods or services were recorded. Our results show that 48% of people who were exposed to the ads made future searches for weight loss information, compared with 32% of those in the control group—a 50% increase. The advertisements varied in efficacy. However, the effectiveness of the advertisements may be greatly improved by targeting individuals based on their lifestyle preferences and/or sociodemographic characteristics, which together explain 49% of the variation in response to the ads. These results demonstrate that online advertisements hold promise as a mechanism for changing population health behaviors. They also provide researchers powerful ways to measure and improve the effectiveness of online public health interventions. Finally, we show that corporations that use these sophisticated tools to promote unhealthy products can potentially be outbid and outmaneuvered.